2019
DOI: 10.1038/s41598-019-42380-x
|View full text |Cite
|
Sign up to set email alerts
|

Single trial prestimulus oscillations predict perception of the sound-induced flash illusion

Abstract: In the sound-induced flash illusion, auditory input affects the perception of visual stimuli with a large inter- and intraindividual variability. Crossmodal influence in this illusion has been shown to be associated with activity in visual and temporal areas. In this electroencephalography study, we investigated the relationship between oscillatory brain activity prior to stimulus presentation and subsequent perception of the illusion on the level of single trials. Using logistic regression, we modeled the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
(58 reference statements)
3
19
1
Order By: Relevance
“…We found that decreased beta power (20-30 Hz) was predictive of correct responses. This fits with results obtained using similar audiovisual simultaneity judgment tasks and with several studies relating b decrease to a better sensory encoding (Griffiths et al, 2019) and b increase to illusory (hence incorrect) perception (for review, see Keil and Senkowski, 2018;Kaiser et al, 2019) . However, one study reported an opposite relationship between accuracy and beta power in a spatial auditory task (Bernasconi et al, 2011), calling for more systematic studies on how the nature of stimuli and task influence the neural generators of relevant beta activity and its influence on performance.…”
Section: Decreased Beta Power Predicts Correct Responsessupporting
confidence: 90%
“…We found that decreased beta power (20-30 Hz) was predictive of correct responses. This fits with results obtained using similar audiovisual simultaneity judgment tasks and with several studies relating b decrease to a better sensory encoding (Griffiths et al, 2019) and b increase to illusory (hence incorrect) perception (for review, see Keil and Senkowski, 2018;Kaiser et al, 2019) . However, one study reported an opposite relationship between accuracy and beta power in a spatial auditory task (Bernasconi et al, 2011), calling for more systematic studies on how the nature of stimuli and task influence the neural generators of relevant beta activity and its influence on performance.…”
Section: Decreased Beta Power Predicts Correct Responsessupporting
confidence: 90%
“…The authors report that increased beta-band power in the STG preceded a multisensory illusion, and that increased beta-band functional connectivity between STG and primary auditory cortex was related to illusion perception on a single trial level. Similarly, Kaiser et al (2019) analyzed single-trial power prior to the SIFI and found that increased beta-and gamma-band power in occipital electrodes predicted the illusion perception. Moreover, using visual and tactile stimuli, Lange et al (2013) found that reduced alpha-band power in visual cortical areas and increased gamma-band power in parietal and temporal cortical areas preceded the illusion, and the authors argued that this reflects cortical excitability.…”
Section: Neural Activity Influences Multisensory Perceptionmentioning
confidence: 99%
“…Mishra et al (2007) found that the proportion of SiFIs perceived ranged from 3 to 86% among individuals. Recent studies have also shown that neural oscillations orchestrate the SiFI effect (Lange et al, 2014;Keil and Senkowski, 2018;Kaiser et al, 2019). Moreover, some studies have indicated that perceptual processing changes dramatically with aging (Cabeza et al, 2004;Salat et al, 2009;Grady, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Existing studies have shown that the SiFI varies across individuals (Keil and Senkowski, 2018;Kaiser et al, 2019). Mishra et al (2007) found that the proportion of SiFIs perceived ranged from 3 to 86% among individuals.…”
Section: Introductionmentioning
confidence: 99%